Analisa Kerusakan Hidrolik Mobil Forklift pada Pengolahan Gabah dan Jagung Menggunakan Fishbone Di PT Seger Agro Nusantara (SAN) - Ismi Mashabai; Silvia Firda Utami; Nurul Hudaningsih; Koko Hermanto (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2024)
As time goes by, more and more new factories appear producing different products. The manufacturing industry is related to tools that support the creation of a corn and grain processing process. PT. Seger Agro Nusantara is a company processing agricultural products such as rice and corn. One of the tools used at PT. Seger Agro Nusantara (SAN) is a forklift to help reduce worker energy in lifting and moving goods. The problem that often occurs with forklifts is the hydraulics. Hydraulics are the main part of a forklift which functions to move, lift and move goods from one place to another. The advantages and disadvantages of hydraulics are that they can transfer large amounts of power using only relatively small components, operate smoothly, do not cause noise or unimportant vibrations in the machine, can be rotated in the reverse direction (reversible), make it easy to move heavy materials in one lift. , or moving goods up to tons in weight. And the service life is quite long, so you can save on the cost of buying new equipment. Meanwhile, the disadvantage is that it requires intensive and regular maintenance. One method that can be used to find the root cause of a problem is a fishbone diagram. Because the fishbone diagram already knows the problem but doesn't know the cause.